Copper-catalyzed direct cyanation of terminal alkynes with benzoyl cyanide. Issue 52 (26th December 2018) - Du, Yan; Li, Zheng
Graphical abstract: Highlights: Less toxic, stable and easy to handle cyanating agent. Air as an oxidant. Mild condition. Up to 85% yield. Abstract: Copper-catalyzed direct cyanation of terminal alkynes is achieved using less toxic, stable and easy to handle benzoyl cyanide as a cyanide source and air as an oxidant. This protocol provides a good alternative to the preparation of 3-arylpropiolonitriles under mild condition.